Hardening of a dual-cure resin cement using QTH and LED curing units - Moraes Coelho Santos, Maria Jacinta; Passos, Sheila Pestana [UNESP]; Lessa da Encarnacao, Monalisa Olga; Santos Junior, Gildo Coelho; Bottino, Marco Antonio [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2010)
Objective: This study evaluated the surface hardness of a resin cement (RelyX ARC) photoactivated through indirect composite resin (Cristobal) disks of different thicknesses using either a light- emitting diode (LED) or quartz tungsten halogen (QTH) light source. Material and Methods: Eighteen resin cement specimens were prepared and divided into 6 groups according to the type of curing unit and the thickness of resin disks interposed between the cement surface and light source. Three indentations (50 g for 15 s) were performed on the top and bottom surface of each specimen and a mean Vickers hardness number (VHN) was calculated for each specimen. The data were analyzed using two-way ANOVA and Tukey-Kramer test was used for post-hoc pairwise comparisons. Results: Increased indirect resin disk thickness resulted in decreased mean VHN values. Mean VHN values for the top surfaces of the resin cement specimens ranged from 23.2 to 46.1 (QTH) and 32.3 to 41.7 (LED). The LED curing light source produced higher hardness values compared to the QTH light source for 2- and 3-mm-thick indirect resin disks. The differences were clinically, but not statistically significant. Increased indirect resin disk thickness also resulted in decreased mean VHN values for the bottom surfaces of the resin cement: 5.8 to 19.1 (QTH) and 7.5 to 32.0 (LED). For the bottom surfaces, a statistically significant interaction was also found between the type of curing light source and the indirect resin disk thickness. Conclusions: Mean surface hardness values of resin cement specimens decreased with the increase of indirect resin disk thickness. The LED curing light source generally produced higher surface hardness values.
Keywords: Hardness; Cure; Resin cements